ReStOre@Home: Feasibility study of a virtually delivered 12-week multidisciplinary rehabilitation programme for survivors of upper gastrointestinal (UGI) cancer - study protocol - Brennan, Louise (My University, 2021)
Background: Exercise rehabilitation programmes, traditionally involving supervised exercise sessions, have had to rapidly adapt to virtual delivery in response to the coronavirus disease 2019 (COVID-19) pandemic to minimise patient contacts. In the absence of an effective vaccine, the pandemic is likely to persist in the medium term and during this time it is important that the feasibility and effectiveness of remote solutions is considered. We have previously established the feasibility of the Rehabilitation Strategies following Oesophago-gastric Cancer (ReStOre) intervention - a face to face multidisciplinary rehabilitation programme for upper gastrointestinal (UGI) cancer survivors. This study will examine the feasibility of a virtually delivered 12-week multi-component ReStOre@Home programme. Methods: This single arm feasibility study will recruit 12 patients who have completed curative treatment for oesophago-gastric cancer. Participants will complete the 12-week ReStOre@Home programme consisting of exercise (aerobic and resistance training), 1:1 dietary counselling and group education sessions through virtual delivery. Underpinned by the Medical Research Council (MRC) Framework, feasibility will be determined by recruitment rates, adherence, retention, incidents, and acceptability. Acceptability will be assessed qualitatively through post-intervention interview and the Telehealth Usability Questionnaire. Secondary outcomes will be assessed pre and post-intervention and will include measures of physical performance (cardiopulmonary exercise test, short physical performance battery, hand grip strength, Godin Leisure Time Questionnaire, and body composition), health related quality of life (European Organisation for Research and Treatment of Cancer Core Quality of Life Questionnaire (EORTC-QLQ-C30) and oesophago-gastric cancer specific subscale (EORTC-QLQ-OG25), fatigue (Multidimensional Fatigue Inventory (MFI-20), and venous blood samples will be collected for the UGI Cancer Survivorship Biobank. Discussion: The ReStOre@Home feasibility study will provide important data regarding the amenability of a multidisciplinary programme designed for UGI cancer survivors to virtual delivery.
PUBLISHED
Keywords: Virtual delivery; Diet; Education; Exercise; Multidisciplinary rehabilitation; Upper gastrointestinal cancer; Cancer; Digital Engagement; Digital Health; REHABILITATION